'Building a safe and resilient Canada': resilience and the mechanopolitics of critical infrastructure. Issue 1 (2nd January 2019) - Boyle, Philip J.
ABSTRACT: This article examines the historical conditions of emergence for the embrace of resilience in the field of critical infrastructure in Canada. Using previously unreleased archival records from the Government of Canada along with contemporary government policies, it traces transformations in how federal planners have sought to diagnose and secure the circulations regarded as essential for life since WWII. It contextualises the embrace of resilience as a recent modulation in these historical processes, one that governs through promoting the adaptive capacities of self-governing entities who operate 'essential' or 'critical' services. This is an articulation of resilience that is compatible with, and extends, wider forms of advanced liberal governance by promoting managerial and technical means for adapting to uncertainty while renouncing responsibility for the integrity of the systems upon which collective vitality depends.